Preparing For the COVID-19 Pandemic: The Perspective of a Department of Anesthesiology in a Tertiary Hospital in Portugal - Fernandes, Sofia (2020)
Since the detection of the first cases of COVID-19, reported by the People’s Republic of China on the 31st December 2019, up to the confirmation of the first cases in Portugal, on the 2nd March, countries like Italy and Spain faced the collapse of their healthcare systems. Anticipating this possibility, the Portuguese National Health Service carried out measures to prepare for this reality. This paper describesthe changes implemented in the Anesthesiology department of a tertiary hospital center in Portugal, aiming to ensure the safety of both patients and healthcare professionals. The measures implemented had to do mostly with scientific preparation and team reorganization; management of personal protective equipment; redesigning the department’s clinical common areas, separation of patient circuits with creation of a designated COVID Operating Room, Post-Anesthetic Care Unit; rescheduling of elective surgery and testing all patients before anesthesia procedures and consulting other hospital departments. The reported data covers the period between the 2nd March and the 30th April of 2020. In this period, 64 cases with COVID-19 or with high clinical suspicion were approached. To date, there have been no cases of in-hospital spread to other patients or to professionals in this department. With this paper we intend to start a reflection that will end up with the optimization of strategies that allows health systems to deal better with COVID-19, keeping patients and health providers safe.